INTEGRATING ‘UNDERLINE’ TECHNOLOGY IN TEACHING ESP REMOTELY - Petrushkova, Anastasiia (The Modern Higher Education Review, 2023)
The article is devoted to the problem of integrating digital tool Underline into the remote classes in the framework of English for specific purposes course (ESP). Underline is a Google Chrome extension that is regarded as a reading tool. It enables students to develop their vocabulary while browsing foreign language content (article, forum etc). The aim of the article is to describe, Underline and assess its effectiveness in ESP remote class. To achieve this goal, we examined the options of Underline precisely and singled out its advantages. When studying the effectiveness of Underline, we conducted a survey based on an anonymous questionnaire created in Google Forms. The research was carried out among the students of 4th year of study of the Institute of Physical Education and Sports during the first semester, the 2023-2024 academic year at LNU Taras Shevchenko National University. The results of the study revealed that Underline facilitates students to process English language content on the Internet greatly. Thus, it has made reading online more enjoyable and attractive. Moreover, it has improved students’ motivation in dealing with reading professionally-oriented texts and contributed to autonomous learning of new words using Underline mobile application.